2009
DOI: 10.1080/13668250802683810
|View full text |Cite
|
Sign up to set email alerts
|

Motor Control Test responses to balance perturbations in adults with an intellectual disability

Abstract: Some adults with an intellectual disability, who have a history of falling, may have delayed responses to postural perturbations and this impairment could be targeted in physiotherapy interventions aimed at improving balance capabilities and preventing falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 6 publications
2
29
1
3
Order By: Relevance
“…They reported that subjects in the ID group had more difficulties motivating themselves, possibly because they did not fully understand the meaning of the testing and therefore might have showed lower performance in this test. Hale et al (2009) experienced similar difficulties when attempting to measure postural balance capabilities in a group of individuals with profound ID.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that subjects in the ID group had more difficulties motivating themselves, possibly because they did not fully understand the meaning of the testing and therefore might have showed lower performance in this test. Hale et al (2009) experienced similar difficulties when attempting to measure postural balance capabilities in a group of individuals with profound ID.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that children with mild ID are markedly inferior compared to nonhandicapped children when performing one foot static balance test (Howe 1959). As analyzed below, more recent studies verify that individuals with ID have a significantly deteriorated balance capacity and reduced ability to respond to external balance perturbations (Carvalho and Almeida 2009;Dellavia et al 2009;Enkelaar et al 2012;Galli et al 2011;Gomes and Barela 2007;Hale et al 2007;Hale et al 2009;Ko et al 1992;Kokubun et al 1997;Lahtinen et al 2007;Okuzumi et al 1997;Rigoldi et al 2011;Smith and Ulrich 2008;Suomi and Koceja 1994;Van De Vliet et al 2006;Van Emmerik et al 1993;Vuijk et al 2010;Webber et al 2004;Yanardag et al 2013). …”
Section: Balancementioning
confidence: 82%
“…Hence, apart from interventions for balance improvement, children with ID and their parents require adoption of injury prevention programs, aiming to learn and implement home and everyday safety strategies that will be useful for their future life (Sherrard et al 2001). Additionally, it has been suggested that the delayed motor responses to balance perturbations shown in adults with ID and a history of falling, should be treated with physiotherapy interventions aiming to improve balance properties and preventing falls (Hale et al 2009). …”
Section: Fall Preventionmentioning
confidence: 98%
See 2 more Smart Citations